Attitudes Toward Water, Sanitation, and Hygiene (WASH) Among Rural and Urban Students in Iringa Region, Tanzania - Magwe, Edward Augustine (AlQalam Journal of Medical and Applied Sciences, 2024)
Students’ attitudes toward Water, Sanitation, and Hygiene (WASH) are influenced by socio-economic conditions, cultural perceptions, and resource availability. Urban students typically access better WASH facilities and education than rural peers. Cultural norms and community involvement play crucial roles in promoting positive hygiene practices and improving health outcomes, especially in Tanzania. The study examined WASH attitudes among students in rural and urban Iringa, Tanzania, highlighting socio-economic influences on these perspectives. This study assessed WASH attitudes among primary and secondary students in rural (Kilolo, Mufindi) and urban (Iringa Municipality) schools in Iringa, Tanzania, from July 4 to 25, 2024. A quantitative analytical cross-sectional design was employed, including 1,536 students randomly selected from 64 schools. Data were collected using structured questionnaires and analyzed by Statistical Package for Social Sciences (SPSS), utilizing descriptive statistics, P-values for associations, and multinomial logistic regression to identify predictors associated with attitudes among students. Rural students have a mean attitude score of 86.38%, slightly higher than urban students at 85.42%. The overall mean attitude score for both groups is 85.90%. It is noteworthy that both rural and urban settings demonstrate a high level of attitude. An independent samples t-test reveals a significant difference (t = -2.067, p = 0.039). In rural areas, 82.4% of students have a high attitude compared to 79.8% in urban areas. Key predictors of WASH attitudes include level of study and type of school, where primary and public-school students revealed significantly higher moderate attitudes, all with (p < 0.05). Rural students exhibit more positive WASH attitudes than urban peers, indicating the need for targeted educational programs and resources to address disparities in various settings highlighted attitude gaps. تتأثر مواقف الطلاب تجاه المياه والصرف الصحي والنظافة الصحية بالظروف الاجتماعية والاقتصادية والتصورات الثقافية وتوافر الموارد. عادةً ما يحصل الطلاب الحضريون على مرافق وتعليم أفضل للمياه والصرف الصحي والنظافة الصحية مقارنة بأقرانهم في المناطق الريفية. تلعب المعايير الثقافية والمشاركة المجتمعية دورًا حاسمًا في تعزيز ممارسات النظافة الإيجابية وتحسين النتائج الصحية، وخاصة في تنزانيا. فحصت الدراسة مواقف المياه والصرف الصحي والنظافة الصحية بين الطلاب في المناطق الريفية والحضرية في إيرينجا، تنزانيا، مع تسليط الضوء على التأثيرات الاجتماعية والاقتصادية على هذه المنظورات. قيمت هذه الدراسة مواقف المياه والصرف الصحي والنظافة الصحية بين الطلاب الابتدائيين والثانويين في المدارس الريفية (كيلوولو، موفيندي) والحضرية (بلدية إيرينجا) في إيرينجا، تنزانيا، من 4 إلى 25 يوليو 2024. تم استخدام تصميم مقطعي تحليلي كمي، بما في ذلك 1536 طالبًا تم اختيارهم عشوائيًا من 64 مدرسة. تم جمع البيانات باستخدام استبيانات منظمة وتحليلها بواسطة الحزمة الإحصائية للعلوم الاجتماعية، باستخدام الإحصاء الوصفي وقيم P للارتباطات والانحدار اللوجستي المتعدد الحدود لتحديد المتنبئين المرتبطين بالمواقف بين الطلاب. يبلغ متوسط درجات المواقف لدى الطلاب الريفيين 86.38٪، وهو أعلى قليلاً من الطلاب الحضريين بنسبة 85.42٪. يبلغ متوسط درجات المواقف الإجمالية لكلا المجموعتين 85.90٪. ومن الجدير بالذكر أن كل من البيئات الريفية والحضرية تظهر مستوى عالٍ من المواقف. يكشف اختبار t للعينات المستقلة عن فرق كبير (t = -2.067، p = 0.039). في المناطق الريفية، يتمتع 82.4٪ من الطلاب بموقف مرتفع مقارنة بـ 79.8٪ في المناطق الحضرية. تشمل المتنبئات الرئيسية لمواقف المياه والصرف الصحي والنظافة مستوى الدراسة ونوع المدرسة، حيث أظهر طلاب المدارس الابتدائية والحكومية مواقف معتدلة أعلى بكثير، وكلها مع (p < 0.05). يظهر الطلاب في المناطق الريفية مواقف أكثر إيجابية تجاه المياه والصرف الصحي والنظافة الصحية مقارنة بأقرانهم في المناطق الحضرية، مما يشير إلى الحاجة إلى برامج وموارد تعليمية مستهدفة لمعالجة التفاوتات في مختلف البيئات التي سلطت الضوء على فجوات المواقف